THE SERUM AND TUMOR TISSUE GASTRIN LEVELS IN PATIENTS WITH GASTRIC AND COLONIC CANCERS - Nihat OKÇU; M. Zeki ALBAYRAK; Leyla YILDIZ; Arif YILMAZ; Mehmet GÜNDOĞDU (Turkish Journal of Gastroenterology, 2020)
-